Evaluasi ketahanan terhadap kekeringan beberapa varietas jagung=Evaluation of Resistance of Several Corn Varieties to Drought Stress - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
. . ABSTRACT The purpose of this research is to evaluate the resistance of several corn varieties to drought stress and to study the correlation among the character measured in the field, pot, and laboratory experiments. The varieties evaluated were nine composite varieties, namely: Arjuna, Harapan, Sadewa, Abimanyu, Bogor Compocite-2, Parikesit, Wisanggeni, Kalingga, and Wiyasa